Cameroon Reunification Fifty (50) Years After: A Systems Approach to How and Why it Endures (African Journal of Law and Politics, 2025)
Literature on how states formerly divided and reunited manage to consolidate reunification is relatively sparse. Even where the history of reunified states is examined, focus is always on the weaknesses of reunification rather than what makes it strong and stable. The purpose of this article is to fill this gap by identifying and explaining the consolidation of reunified States. Using the example of the State in Cameroon, it finds that the consolidation of reunification is a constructive and systematic political process characterised by attempts to neutralise potentials of differentiation that could lead to demands for separation. It is a dynamic political process that has involved a negotiated federation, a merger of political parties, formation of a unitary state, constructing and forging a national discourse of unity and integration and the threat of use of legitimate violence and intimidation. The paper reveals the capability of political systems in terms of ensuring their survival under vulnerable and fragile conditions.